2010
DOI: 10.1016/j.jvs.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transposition of the left renal vein into the inferior vena cava for nutcracker syndrome

Abstract: Reimplantation of the left renal vein into the infrarenal inferior vena cava is the standard surgical procedure for nutcracker syndrome. A 40-year-old woman with a solitary left kidney suffered from left lumbar pain and hematuria. Imaging techniques found a large kidney with nutcracker syndrome. A totally laparoscopic transposition of the left renal vein was performed. Twelve months later, the patient is improved and has no more hematuria. Duplex scan showed no residual stenosis. Laparoscopic transposition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…However, the outcomes of laparoscopic procedures reported in the literature are comparable with those of open procedures; these include laparoscopic spleno-renal venous bypass and laparoscopic LRV-IVC transposition, with the latter avoiding complications to the spleen from ischaemia and tears, 60,62 as it bypasses the portal venous circulation where pressure is higher than central venous pressure, hence maintaining LRV hypertension. 62 Chung et al found that after laparoscopic spleno-renal venous bypass surgery the luminal diameter of the splenic vein increased to twice its normal diameter once unclamped. 60 In terms of outcomes, at 8 months' follow-up the patient's chronic left flank pain improved with no need for analgesia.…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the outcomes of laparoscopic procedures reported in the literature are comparable with those of open procedures; these include laparoscopic spleno-renal venous bypass and laparoscopic LRV-IVC transposition, with the latter avoiding complications to the spleen from ischaemia and tears, 60,62 as it bypasses the portal venous circulation where pressure is higher than central venous pressure, hence maintaining LRV hypertension. 62 Chung et al found that after laparoscopic spleno-renal venous bypass surgery the luminal diameter of the splenic vein increased to twice its normal diameter once unclamped. 60 In terms of outcomes, at 8 months' follow-up the patient's chronic left flank pain improved with no need for analgesia.…”
Section: Surgical Managementmentioning
confidence: 99%
“…14 Hartung et al reported successful outcomes at 12 month follow-up following laparoscopic transposition of the LRV into the inferior vena cava for a 40 year old lady where disabling pain in the left lumbar region and haematuria resolved, and on duplex ultrasound the reconstruction remained patent. 62 Compared with the clamping technique employed by Chung et al, which led to a total ischaemia time interval of 37 minutes, 60 the technique carried out by Hartung et al had no ischaemic period because of clamping the LRV on the right side of the left ovarian vein. 62 Numerous other laparoscopic techniques have been carried out to treat NCS.…”
Section: Surgical Managementmentioning
confidence: 99%
“…6,7 The originality of our technique was that we performed both these steps at one time. A large dissection of the LRV trunk and sectioning the LRV trunk collaterally were necessary to perform the transposition without tension on the sutures.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of laparoscopic transposition of the LRV for NCS was reported by Hartung et al [8 ]in 2010 and was performed via a transperitoneal approach from the left side. In our study, a retroperitoneal approach from the right side was used to complete the laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical procedures have been described such as endovascular stenting [2], external stenting of the LRV [3], splenorenal venous bypass [4], inferior mesenteric-gonadal vein bypass [5] and transposition of the SMA [6] or LRV [1,7]. Among these procedures, reimplantation of the LRV into the distal inferior vena cava (IVC) is considered to be the gold standard method to treat NCS [8]. The majority of conventional procedures for correcting NCS are performed via open surgery.…”
Section: Introductionmentioning
confidence: 99%